Experimental Characterization of Polyurethane Foam Deformation During Bra Cup Moulding (Journal of Fiber Bioengineering and Informatics, 2014)
The paper develops a novel method to explore a suitable scanning installation to reduce deformationeffect of foam cups under different moulding conditions, and proposes a quantitative assessment indexfor the geometric shape of foam cups via non-contact three-dimensional scanning. Two kinds of foamswith different performance behaviour were selected for moulding test. Depending on the Box-Behnkendesign, a total of 12 foam cups in size 34B, 36C and 36DD for each type of foam material were scanned inthe bird-view and upward-view positions for comparative purposes. Through a two tailed paired t-testand Pearson's correlation testing results, the most effective foam deformation index was confirmed firstlyto assess the quality of the foam cups. The result shows that the deformation between moulded cupand its plastic shot scanned in the bird-view position is consistently less than that in the upward-viewposition. The amount of dwell time significantly affects the deformation for the two types of foam cups.